2008
DOI: 10.1007/s10350-008-9194-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Pouchitis after Ileal Pouch-Anal Anastomosis: A Retrospective Review

Abstract: Chronic pouchitis is a frequent complication after ileal pouch-anal anastomosis. In this study patients with primary sclerosing cholangitis or other extraintestinal manifestations of ulcerative colitis were not more likely to develop chronic pouchitis. Patients with postoperative complications, specifically anastomotic complications after ileal pouch-anal anastomosis, were more likely to develop chronic pouchitis and may benefit from early strategies to prevent pouchitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(49 citation statements)
references
References 15 publications
3
44
0
2
Order By: Relevance
“…Pouchitis occurs in up to 60 % of patients aft er a mean follow-up of 40 months ( 334,335 ) and occurs more frequently in patients with PSC, preoperative EIMs ( 336 -338 ), and in patients who had never smoked ( 339 ). Chronic pouchitis may be more likely to occur in those patients with early postoperative anastomotic complications ( 340 ).…”
Section: Recommendations For Surgerymentioning
confidence: 99%
“…Pouchitis occurs in up to 60 % of patients aft er a mean follow-up of 40 months ( 334,335 ) and occurs more frequently in patients with PSC, preoperative EIMs ( 336 -338 ), and in patients who had never smoked ( 339 ). Chronic pouchitis may be more likely to occur in those patients with early postoperative anastomotic complications ( 340 ).…”
Section: Recommendations For Surgerymentioning
confidence: 99%
“…Genetic polymorphisms, extraintestinal manifestations, the presence of serum perinuclear antineutrophil cytoplasmic antibodies, backwash ileitis, thrombocytosis, non-smoking behaviour, extensive UC and the use of NSAIDs are some of the previously identified risk factors for pouchitis [8]. A retrospective review by Hoda et al [9] found that patients who did not undergo diverting ileostomy at the time of the IPAA and those with postoperative complications were more likely to develop chronic pouchitis, whereas primary sclerosing cholangitis and extraintestinal manifestations -known predictors for acute pouchitis -did not trend toward a higher likelihood of developing chronic pouchitis.…”
Section: Discussionmentioning
confidence: 99%
“…Pouchitt, definert som økende avføringsfre-kvens, endret avføringskonsistens, blodig avføring og smerter av varighet i over to døgn, sammenholdt med funn ved reservoarskopi, ble sett hos 30 % av pasientene. I andre undersøkelser har det vaert pouchitt hos opptil 60 % av pasientene under en oppfølgingstid på opp mot 20 år (1,4,8,9). År-saken til at vi har hatt mindre pouchitt kan vaere kortere observasjonstid (median 109 md.).…”
Section: Diskusjonunclassified
“…Ut fra prospektive studier med lang observasjonstid (opp mot 20 år) er det også antydet en mulig tendens til dårligere funksjonelle resultater over tid, det gjelder da spesielt lekkasjeproblemer (5,16). Det samme er tilfellet for lokale komplikasjonerførst og fremst pouchitt, der man vet at forekomsten øker med økende observasjonstid (1,4,8,9,17). Når en pasient mister reservoaret etter lengre tid, skyldes det som oftest kronisk pouchitt (6).…”
Section: Diskusjonunclassified